Key factors for successful implementation of the independent curriculum: examining teacher readiness - Retnowati, Ayu Ana Fitri; Triyanto, Triyanto; Matsuri, Matsuri (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The Merdeka Curriculum that prioritizes student autonomy in the learning process was chosen as a solution to overcome the learning crisis exacerbated by the Covid-19 pandemic. However, the implementation of this curriculum faces challenges, especially related to teacher readiness. This study aims to analyze factors that affect teacher readiness in implementing the "Merdeka" curriculum, including teacher understanding of curriculum steps, lesson plan readiness, and supporting and inhibiting factors. This research uses a qualitative approach with a case study design involving grade 1 to 6 teachers who have implemented the "Merdeka" curriculum. Data were collected through interviews, observation, and documentation, and analyzed using inductive models. The results of the study explained that although teachers have a good understanding of the seven steps in implementing the curriculum, there are still challenges in realizing planned learning due to the dominance of lecture teaching styles. Several inhibiting factors were identified, including lack of pedagogic competence, limited facilities and infrastructure, and insufficient number of teachers. On the other hand, supporting factors such as school funding, teacher working groups, and collaboration among teachers have been shown to contribute to successful implementation. The implications of this study emphasize the need for targeted professional development programs, adequate funding and infrastructure support, and the value of collaboration among teachers.